Whole-genome sequencing of multidrug resistance Salmonella Typhi clinical strains isolated from Balochistan, Pakistan - Fatima, Sareen; Ishaq, Zaara; Irfan, Muhammad; AlAsmari, Abdullah F.; Achakzai, Jahangir Khan; Zaheer, Tahreem; Ali, Amjad; Akbar, Ali (Frontiers in Public Health, 2023)
Salmonella enterica serovar typhi (S. typhi) is a major cause of morbidity and mortality in developing countries, contributing significantly to the global disease burden. In this study, S. typhi strains were isolated from 100 patients exhibiting symptoms of typhoid fever at a tertiary care hospital in Pakistan. Antimicrobial testing of all isolates was performed to determine the sensitivity and resistance pattern. Three MDR strains, namely QS194, QS430, and QS468, were subjected to whole genome sequencing for genomic characterization. MLST analysis showed that QS194, belonged to ST19, which is commonly associated with Salmonella enterica serovar typhimurium. In contrast, QS430 and QS468, belonged to ST1, a sequence type frequently associated with S. typhi. PlasmidFinder identified the presence of IncFIB(S) and IncFII(S) plasmids in QS194, while IncQ1 was found in QS468. No plasmid was detected in QS430. CARD-based analysis showed that the strains were largely resistant to a variety of antibiotics and disinfecting agents/antiseptics, including fluoroquinolones, cephalosporins, monobactams, cephamycins, penams, phenicols, tetracyclines, rifamycins, aminoglycosides, etc. The S. typhi strains possessed various virulence factors, such as Vi antigen, Agf/Csg, Bcf, Fim, Pef, etc. The sequencing data indicated that the strains had antibiotic resistance determinants and shared common virulence factors. Pangenome analysis of the selected S. typhi strains identified 13,237 genes, with 3,611 being core genes, 2,093 shell genes, and 7,533 cloud genes. Genome-based typing and horizontal gene transfer analysis revealed that the strains had different evolutionary origins and may have adapted to distinct environments or host organisms. These findings provide important insights into the genetic characteristics of S. typhi strains and their potential association with various ecological niches and host organisms.